Barley lesion mimics, supersusceptible or highly resistant to leaf rust and net blotch. (7th November 2012) - Wright, S. A. I.; Azarang, M.; Falk, A. B.
Abstract : Lesion mimic mutants of plants have the feature of spontaneously displaying necrotic spots or bands on their leaves. Lesion mimics have often displayed enhanced resistance to biotrophic pathogens whilst showing increased susceptibility to necrotrophs. This paper identifies three novel, non‐allelic mutants of barley ( Hordeum vulgare ), which spontaneously form necrotic leaf lesions: Necrotic leaf spot 9.3091 ( nec9 . 3091 ), Mottled leaf 8.1661 ( mtt8 . 1661 ) and Mottled leaf 9.2721 ( mtt9 . 2721 ). The Necrotic leaf spot 8.3550 mutant ( nec8 . 3550 ), formerly known as bst1, was included in the study because it is a lesion mimic mutant belonging to the same original pool. The reactions of the mutants to the biotroph Puccinia hordei and the necrotroph Pyrenophora teres f. sp . teres were investigated. Mutants nec8 . 3550 and mtt8 . 1661 were more resistant than the parental Bowman near‐isogenic line with the Rph3.c gene (Bowman Rph3.c, NGB 22452) to leaf rust, caused by P. hordei . Mutants nec8 . 3550, mtt8 . 1661 and mtt9 . 2721 were more susceptible than Bowman Rph3.c to net blotch, caused by P. teres f. sp. teres . Autofluorescence was detected in leaf tissues of all mutants. Based on the high expression of the PR1 and Hv‐HIR genes, combined with the low susceptibility to P. hordei, nec8 . 3550 appears to have entered a state of systemic acquired resistance, which is quite distinct from the resistance expressed in mtt8 . 1661 . The latter mutant has low or no expression of PR1 and Hv‐HIR genes, yet it is highly resistant to rust. It is also extremely susceptible to net blotch. These mutants can serve as genetic sources of novel disease resistance for barley improvement.